Kontribusi Komunikasi Interpersonal dan Bimbingan Belajar Orang Tua Terhadap Prestasi Belajar Siswa Kelas V Di SD Unggulan Daar El Dzikir Bulu Kabupaten Sukoharjo TahunPelajaran 2015/2016 - Sary, Tutut Anita, Dr. Achmad Fathoni (2016)
The purpose of this study was to determine include: 1) Contributions of interpersonal communication on a class V student achievement in elementary school Unggulan Daar El Dzikr Sukoharjo district in the academic year 2015/2016, 2) Contributions tutoring parents on a class V student achievement in elementary school Unngulan Daar El Dzikir Bulu Sukoharjo district in the academic year 2015/2016, 3) Contributions of interpersonal communication and guidance of parents on class V student achievement in elementary school Unggulan Daar El Dzikir Bulu Sukoharjo district in the academic year 2015/2016. This type of research is based on a quantitative approach to the type of research Ex-Post Facto. The analysis technique used is t test, test F. Based on the analysis of data: 1) Test Results thitung interpersonal communication t (3.544)> t table (2.052), interpersonal communication has contributed positively to student achievement. 2) tutoring parents contribute positively to student achievement, it is based on t test results tcount (3.436)> t table (2.052). 3) The test results f significance value 0.000 <0.05, means of interpersonal communication and tutoring together contribute positively to student achievement on a V class student achievement in elementary school Unggulan Daar El Dzikr Sukoharjo district in the academic year 2015/2016.